Source mechanism of the July 13, 2002 Earthquake Kingri, Balochistan - Mahmood, Tariq; Qaisar, Mohammad (Journal of Himalayan Earth Sciences, 2002)
Teleseismic body Waves recorded at worldwide 12digital seismic stations were used to study the source process of the July 13, 2002 earthquake that occurred near Kingri, Baluchistan, The P and SH waveforms of this event recorded by IRIS Digital Global Seismographic Network were inverted to double couple source using the method of Kikuchi and Kanamori (1986). The azimuthal coverage of seismograph stations is good enough to resolve some details of heterogeneous moment tensor. The focal mechanism solution shows strike slip faulting having strike 144.6o, dip 31.5o, and rake -7o. The seismic moment is estimated as 3.2 x 1017Nm. The solution of the event is compared with fault plane solution derived from first motion polarity data recorded by local seismic network and also with the Harvard CMT solution. The moment tensor solution is in agreement with those obtained from first motion polarity and CMT solution.